Valuation of trips to second homes : do environmental attributes matter? - Huhtala, Anni; Lankia, Tuija (Routledge, 2012)
We use Finnish data to estimate the extent of the recreation benefits obtained from visits to second homes. Special emphasis is placed on how environmental attributes of second homes influence the recreation value of visits. The impacts are valued using the travel cost method. We estimate the recreation value to be about approximately (sic)170-205 per trip. The aggregate non-market benefits of the use of the current summer home stock are considerable - approximately (sic)500 million per annum. The presence of algae that prevent aquatic recreation decreases the value per trip by 40%, and the lack of a beach reduces it by 45%; electrification increases the value by 3-5%. These impacts should be balanced against the social costs of second homes when designing environmental policies on leisure-time housing.
Keywords: Ma; Suomi; loma-asunnot; ympäristövaikutukset; recreation; travel costs; demand; benefits